Pattern of Antibiotic Sensitivity in Enteric Fever: A Tertiary Care Hospital Experience (Journal of Medicine, 2014)
Objectives: To describe the antibiotic sensitivity pattern ofSalmonella typhi and Salmonella paratyphi from blood culture specimens. Methods: This cross-sectional study was done in the Department of Medicine, BIRDEM from July 2009 to June 2012. Standard laboratory and microbiological procedures were followed for blood culture and antibiotic sensitivity tests. Results: Among the 97 blood culture positive samples, S. typhi was 71 (73.2%) and S. paratyphi was 26 (26.8%). Multi-drug resistant strains of S. typhi and S. paratyphi were 23 (32.4%) and 3 (11.5%) cases respectively. Azithromycin, nalidixic acid, ciprofloxacin, levofloxacin and amoxicillin resistance was also found in a good number of cases (S. typhi and S. paratyphi: 71.8% and 57.7%, 42.3% and 30.8%, 38% and 34.6%, 38% and 26.9% and 38% and 26.9% cases respectively). Nineteen (31.1%) of the 61ciprofloxacin sensitive organisms were resistant to nalidixic acid. Ceftriaxone was sensitive in 100% of S. typhi and S. paratyphi. Cefixim, ciprofloxacin, levofloxacin, imipenem were among the most common sensitive antibiotics (S. typhi and S. paratyphi: 83.1% and 73.1%, 62% and 65.4%, 53.5% and 65.4%, 76.1% and 65.4% cases respectively). Conclusion: Ceftriaxone was the most sensitive antibiotic for treating enteric fever followed by cefixim, imipenem and ciprofloxacin. However, in suspected cases of enteric fever, blood culture should be requested before prescribing antibiotic.DOI: http://dx.doi.org/10.3329/jom.v15i2.20684 J MEDICINE 2014; 15 : 122-124